Interrogation in Teacher-Student Interaction in Bahasa Indonesia Learning at Elementary School - Akmal Hamsa; Sultan Sultan (Intelektual Pustaka Media Utama, 2014)
Interrogation in Teacher-Student Interaction in Bahasa Indonesia Learning at Elementary School. This study aimed to describe the form, function, and questioning strategies teachers in teacher-student interrogation in Bahasa Indonesia learning in elementary school. Data sourced from four teacher of elementary school, SDN Tamangapa and SD Inpres Tamangapa. Data were obtained by (1) recording, (2) documentation, (3) field notes, (4) interview. The results showed that: (1) the form of questioning the teacher in the teacher-student interaction in Bahasa Indonesia learning in primary schools generally examined the low-level thinking skills, (2) functions of teacher questions are generally intended to check student understanding, and (3) teachers utilize a variety of strategies in addressing student answers correctly and the apparent hesitation. Some disadvantages are indicated teachers in providing interrogation.